Electronic service quality in online shopping and risk reduction strategies. Issue 3 (5th August 2014) - Vos, Angeliki; Marinagi, Catherine; Trivellas, Panagiotis; Eberhagen, Niclas; Giannakopoulos, Georgios; Skourlas, Christos
Abstract : Purpose: – The purpose of this paper is to investigate risk reduction strategies in online shopping through the perspective of buyer's trust. Design/methodology/approach: – An explanatory research approach is adopted to identify cause-and-effect relationships between e-quality and customers' loyalty, satisfaction and trust. This approach is accomplished through field research, which is based on a structured questionnaire that utilizes the E-S-QUAL tool, which is a multiple-item general scale for measuring electronic service quality. The sample is consisted of 92 e-buyers (consumers). Findings: – The field research revealed that three e-quality dimensions, namely, ease of use, customization and assurance, e-scape and responsiveness, have significant positive effects on e-loyalty and e-satisfaction. Regarding e-trust, only customization and assurance exerts a significant positive effect. Research limitations/implications: – The field research provides in-depth understanding of relationships among e-loyalty, e-satisfaction and e-trust. The majority of the respondents are young people living in Athens, Greece, highly educated, with a relative low monthly income. Originality/value: – This study investigates how trust is affecting the consumers' engagement to e-commerce, suggesting the appropriate security that should be taken to mitigate perceived risks. Reviewing security measures can help reduce risks of an e-company and simultaneously enforce the level of trust and customers' intentions to buy.